Alerting people prioritising territories over technologies. A design framework for local decision makers in France. (September 2022) - Bopp, Esteban; Douvinet, Johnny
Abstract: Public alerting is a major challenge in a world where risks and communication modes are constantly evolving. Since a few years, new massive alerting tools geolocating the population in real time (Cell Broadcast or Location-Based SMS) have been deployed at national level in several countries. However, this evolution does not always reach with local needs. Decision-makers can use a wide multiplicity of tools and this can induce vulnerability differences from one territory to another. To help decision makers in their choice of equipment, this study proposes a Spatial Decision Support System and applied it in 40 various French municipalities in order to observe how 13 alerting tools are adapted (or not) to the characteristics of the municipalities. Early findings highlighted a great diversity of adapted tools between municipalities and within municipalities, in different alert zones. Alerting tool equipment must be considered at an infra-municipal scale to fully consider the diversity of alert zones. The greater the number of inhabitants, the more diverse the alerting tools needed. Also, few tools are suitable for municipalities with a low population and poor access to telecommunication networks. Finally, as tools geolocating individuals are suitable for highly populated municipalities, such national equipment shall not be used on small alert zones involving few individuals. Highlights: Facing disasters, characteristics of territories influence the alerting tools required. A spatial decision support system is applied to see how 13 alerting tools fit in 40 French municipalities. The greater the number of inhabitants, the more diverse the alerting tools needed. National LBAS (Location-Based Alerting Systems) are poorly adapted to municipal scale. Few tools are suitable for municipalities with a low population and poor access to telecommunication networks.